Secret of the spa - Keene, Carolyn (Keene, Carolyn., 2005)
When a new spa in town has its grand opening, Nancy gets tickets for herself and her best friends, George and Bess, to attend. However, it appears someone is tampering with the food and stinking up the business. Nancy is determined to sniff it out. When I scored tickets to the grand opening of a new spa in town, I knew I had to take Bess. George came along, too, but she's been acting so weird. I knew this wouldn't be her idea of a total blast, but she's just been no fun at all. It's unlike her to be such a grouch! But then, this new spa isn't turning out to be much fun, either. Deirdre's here, for starters. And someone's tampering with the food, and trying to take the "luxury" out of this otherwise luxurious place. Something stinks in this spa, and if I can't sniff it out, my name's not Nancy.